Endothelin‐1 Drives Epithelial‐Mesenchymal Transition in Hypertensive Nephroangiosclerosis - Teresa M. Seccia; Brasilina Caroccia; Francesca Gioco; Maria Piazza; Valentina Buccella; Diego Guidolin; Eugenia Guerzoni; Barbara Montini; Lucia Petrelli; Elisa Pagnin; Verdiana Ravarotto; Anna S. Belloni; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundTubulointerstitial fibrosis, the final outcome of most kidney diseases, involves activation of epithelial mesenchymal transition (EMT). Endothelin‐1 (ET‐1) activates EMT in cancer cells, but it is not known whether it drives EMT in the kidney. We therefore tested the hypothesis that tubulointerstitial fibrosis involves EMT driven by ET‐1. Methods and ResultsTransgenic TG[mRen2]27 (TGRen2) rats developing fulminant angiotensin II–dependent hypertension with prominent cardiovascular and renal damage were submitted to drug treatments targeted to ET‐1 and/or angiotensin II receptor or left untreated (controls). Expressional changes of E‐cadherin and α‐smooth muscle actin (αSMA) were examined as markers of renal EMT. In human kidney HK‐2 proximal tubular cells expressing the ETB receptor subtype, the effects of ET‐1 with or without ET‐1 antagonists were also investigated. The occurrence of renal fibrosis was associated with EMT in control TGRen2 rats, as evidenced by decreased E‐cadherin and increased αSMA expression. Irbesartan and the mixed ET‐1 receptor antagonist bosentan prevented these changes in a blood pressure–independent fashion (P < 0.001 for both versus controls). In HK‐2 cells ET‐1 blunted E‐cadherin expression, increased αSMA expression (both P < 0.01), collagen synthesis, and metalloproteinase activity (P < 0.005, all versus untreated cells). All changes were prevented by the selective ETB receptor antagonist BQ‐788. Evidence for involvement of the Rho‐kinase signaling pathway and dephosphorylation of Yes‐associated protein in EMT was also found. ConclusionsIn angiotensin II–dependent hypertension, ET‐1 acting via ETB receptors and the Rho‐kinase and Yes‐associated protein induces EMT and thereby renal fibrosis.